2020 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining (ASONAM) 2020
DOI: 10.1109/asonam49781.2020.9381379
|View full text |Cite
|
Sign up to set email alerts
|

The Ivory Tower Lost: How College Students Respond Differently than the General Public to the COVID-19 Pandemic

Abstract: In the United States, the country with the highest confirmed COVID-19 infection cases, a nationwide social distancing protocol has been implemented by the President. Following the closure of the University of Washington on March 7th, more than 1000 colleges and universities in the United States have cancelled in-person classes and campus activities, impacting millions of students. This paper aims to discover the social implications of this unprecedented disruption in our interactive society regarding both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 8 publications
(16 reference statements)
1
59
1
3
Order By: Relevance
“…Statistically significant but small-magnitude associations of negative sentiment scores relative to positive scores with greater financial stress and lower Knowledge of community sentiment during public health events can inform better health outcomes by providing insights into the psychosocial and environmental drivers of human behavior and in detecting unanticipated events or trends within the community [35]. Similar to previous research [36][37][38], our findings suggest an overall trend toward neutral and negative sentiment toward COVID-19. Neutral sentiment tends to indicate lower levels of concern about COVID-19 or minimal experiences of personal impact.…”
Section: Principal Findingssupporting
confidence: 78%
“…Statistically significant but small-magnitude associations of negative sentiment scores relative to positive scores with greater financial stress and lower Knowledge of community sentiment during public health events can inform better health outcomes by providing insights into the psychosocial and environmental drivers of human behavior and in detecting unanticipated events or trends within the community [35]. Similar to previous research [36][37][38], our findings suggest an overall trend toward neutral and negative sentiment toward COVID-19. Neutral sentiment tends to indicate lower levels of concern about COVID-19 or minimal experiences of personal impact.…”
Section: Principal Findingssupporting
confidence: 78%
“…Where the psychological impact of the pandemic in education was a concern, the existing literature has tended to focus on the student population. A topical analysis of tweets (Duong et al, 2020) revealed that negative sentiments toward the central issues of COVID-19 were significantly higher among students than in the general population. Khodabakhshi-Koolaee (2020) in interviews with 15 postgrad students in Iran who had experienced living in quarantine, as three of the four main emerging themes identified (i) developing negative emotions, confusion and pessimism, (ii) concerns about family health, as well as (iii) economic and social concerns and "fear of tomorrow."…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent survey study of a group of Chemistry students at the University of British Columbia by [33] reveals that their experience with transitioning to ERT was mostly negative, with students complaining about lack of motivation and interaction with classmates and instructors . Another study of students' sentiment on Twitter by [14] found that college students were "likely to express negative feelings towards how social distancing and school closure are affecting their work and study environments", and a majority of them (81.3%) disliked remote learning. Common issues were difficulty learning subjects that would require physical interaction with the content (i.e., chemistry and biology laboratories) and keeping up with the course pace when attendance to weekly lectures was no longer required, as was already found in pre-COVID studies [16,31].…”
Section: Learning During the Covid-19 Pandemicmentioning
confidence: 99%